A short review on biomass thermo chemical conversion: recent advances - Othaman, Muhamad Fazli; Sabudin, Sulastri; Mohideen Batcha, MohdFaizal (Engg Journals Publications, 2016)
Biomass is long known as a viable source of fuel. However, the industrial revolution has changed mankind’s dependence on fossil fuels until today. The depletion of the fossil fuel sources and it is escalating price encouraged many research works since two decades agoin the bid to replace fossil fuel with biomass. Biomass has now became an importantenergy source because of its extensive spread availability and promising potential to reduce global warming. Thermo-chemical conversion of biomass yield variety of solid, liquid and gaseousfuels and have equal importance both at industrial and environmental conservation aspects. This paper provides a review on several thermo-chemical conversion routes of biomass. The technologies of combustion, gasification, pyrolysis, liquefaction and carbonization is reviewed in this paper and highlighting each of their unique advantages. The benefits of biomass cofiring with fossil fuels were also highlighted in this paper.